Convergence and Divergence in United States and Canadian Cuba Policy Post-1959: A Triangular Comparative Analysis - Rodríguez, Raúl (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2008)
The main objective of this article is to explore the convergence and divergence in both of these North American nations' Cuba policy. The last 49 years have been full of important and dramatic economic, political, military, and socio-cultural events worldwide that have had an impact on this triangular relationship. Therefore, even the smallest attempt at covering all aspects over such a long period would be worthy of a much lengthier piece of writing. However, an overview of the post-1959 period reveals a remarkable continuity in American Cuba policy. The main objective of successive United States governments, both Republican and Democrat, has been regime change by using a full arsenal of overt and covert means, while Canadian policy has diverged mostly in terms of the means to promote the desired changes that would bring Cuba back to the pattern of Western socio-economic capitalist formation. This article is mainly the result of a study of the initial years of the Cuban revolution, from 1959 to 1962, that were full of defining and transformational events. These events set the tone for the years to come against the backdrop of the prevailing order of international relations resulting from the Second World War and the Cold War.